INTEGRATING SHADOWING, ANTICIPATION, AND REFORMULATION INTO A COMPREHENSIVE INTERPRETER TRAINING CURRICULUM - Saidova , Marjona (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This study investigates the role of shadowing, anticipation, and reformulation in interpreter training and analyzes how their integration can improve the overall interpreting performance of students. The research is based on theoretical studies in interpreting pedagogy and the analysis of practical training exercises used in interpreter courses. The results show that combining these techniques helps students develop automaticity, increase processing speed, and reduce cognitive load during simultaneous interpreting. The study also highlights the importance of systematic training and gradual skill development in interpreter education.The findings suggest that an integrated approach to interpreter training is more effective than teaching each skill separately. The proposed model may be useful for interpreter trainers, students, and researchers interested in improving interpreting methodology.